Reconstructing Proportional Justice in Islamic Family Law: Post-Divorce Marital Property Distribution in Mandailing Natal from the Perspective of Maqāṣid al-Usrah - Zuhdi Hasibuan; Asrul Hamid; Andri Muda Nst; Raja Ritonga; Idris Idris (Hukum Keluarga Islam IAIN LANGSA, 2026)
This study critically examines the normative framework of Article 97 of the Indonesian Compilation of Islamic Law (KHI), which regulates an equal (50:50) division of marital property upon divorce, through a socio-legal perspective focusing on cases involving unemployed husbands in Mandailing Natal Regency. While existing scholarship has primarily emphasized doctrinal interpretation and procedural aspects of joint property classification, limited attention has been given to how formal legal norms operate within contexts of structural economic inequality and differentiated spousal contributions. Furthermore, empirical assessments of proportional justice in the application of Article 97 remain underdeveloped. To address this gap, this research adopts a mixed normative-empirical approach by integrating doctrinal legal analysis with field data from Mandailing Natal Regency. The empirical material consists of thirteen divorce cases and in-depth interviews with twelve key informants. The data are analyzed through a socio-legal interpretive framework that juxtaposes normative legal provisions with lived socio-economic realities. The study is theoretically grounded in maqāṣid al-Usrah as an extension of maqāṣid al-shariah, which is operationalized as an evaluative framework for assessing substantive fairness in Islamic family law. The findings indicate that, within the observed cases, the strict application of Article 97 tends to produce outcomes that insufficiently reflect the differentiated financial and non-financial contributions of spouses, particularly in situations where wives bear dual domestic and economic responsibilities. This study contributes theoretically by advancing maqāṣid al-Usrah as an operational analytical tool in socio-legal inquiry, and empirically by providing context-specific evidence from Mandailing Natal that evaluates the adequacy of the equal-sharing principle under conditions of economic asymmetry. The findings suggest that proportional justice offers a more context-sensitive interpretive approach for marital property division while remaining aligned with the normative objectives of maṣlaḥah and al-‘adālah. The study concludes that a context-sensitive interpretive refinement of Article 97 may be warranted, particularly by considering verifiable spousal contributions as a basis for more substantively equitable outcomes in post-divorce property distribution.